Dynamics of Live-Stream Commerce: Unveiling External and Internal Factors in Impulse Buying Decisions in Live Shopping - Ronny Albar Mahendra; Yudhistira Bawa Yusha; Maria Anisa Naulita; Evi Rinawati Simanjuntak (Eduvest - Journal of Universal Studies, 2024)
The development of internet technology has encouraged innovation in digital commerce, especially e-commerce. One of the rapidly growing trends is live shopping, which combines social media interactivity with a real-time shopping experience. This study aims to explore the influence of internal and external factors on impulse purchase decisions in the context of live shopping. Using a quantitative approach and modeling of structural equations (Partial Least Squares-Structural Equation Modeling/PLS-SEM - Smart PLS 4.0.), data was collected from 300 respondents in Indonesia through an online survey. The results showed that external factors, such as streamer attractiveness, content quality, and perceived interactivity, significantly increased perceived enjoyment. However, perceived enjoyment has not been proven to significantly encourage impulse purchasing decisions. Conversely, internal factors, such as hedonistic motivation, viewing frequency, and impulse buying tendencies, have been shown to have a strong influence on impulse purchases during live shopping sessions. The study concluded that while external factors can create a pleasurable experience, they do not directly trigger impulsive buying behavior in the absence of internal impulses. These findings provide new insights for marketers to design effective strategies that focus more on the psychological aspects of consumers, such as hedonistic motivation and increased frequency of interactions, to encourage engagement and impulse purchases in live shopping platforms